Emergency preparedness: What is the future? - Jocelyn J. Herstein; Michelle M. Schwedhelm; Angela Vasa; Paul D. Biddinger; Angela L. Hewlett (Cambridge University Press, 2021)
Emergency preparedness programs have evolved over the last several decades as communities have responded to natural, intentional, and accidental disasters. This evolution has resulted in a comprehensive all-hazards approach centered around 4 fundamental phases spanning the entire disaster life cycle: mitigation, preparedness, response, and recovery. Increasing frequency of outbreaks and epidemics of emerging and reemerging infectious diseases in the last decade has emphasized the significance of healthcare emergency preparedness programs, but the coronavirus disease 2019 (COVID-19) pandemic has tested healthcare facilities' emergency plans and exposed vulnerabilities in healthcare emergency preparedness on a scale unexperienced in recent history. We review the 4 phases of emergency management and explore the lessons to be learned from recent events in enhancing health systems capabilities and capacities to mitigate, prepare for, respond to, and recover from biological threats or events, whether it be a pandemic or a single case of an unknown infectious disease. A recurring cycle of assessing, planning, training, exercising, and revising is vital to maintaining healthcare system preparedness, even in absence of an immediate, high probability threat. Healthcare epidemiologists and infection preventionists must play a pivotal role in incorporating lessons learned from the pandemic into emergency preparedness programs and building more robust preparedness plans.